Clinical sleep medicine : a comprehensive guide for mental health and other medical professionals - During, Emmanuel H., 1976-; Kushida, Clete Anthony, 1960- (American Psychiatric Association Publishing, 2021)
"The importance of sleep for well-being and general and mental health is increasingly being recognized. Sleep complaints are commonly associated with mental disorders and are even part of the diagnostic criteria for some of them, such as mood and anxiety disorders and PTSD. The relationship between sleep and psychiatric disorders is intertwined and, in some cases, bidirectional. Anxiety, psychosis, and depression often result in reduced sleep quality (sleep fragmentation, experience of unpleasant, unrefreshing sleep), quantity (increased or reduced), or pattern (changes in sleep schedule, loss of sleep consistency). Reciprocally, sleep disorders can contribute to the exacerbation of psychiatric symptoms and independently affect the prognosis. Finally, most psychotropic drugs have an effect on sleep and arousal and can aggravate a preexisting sleep abnormality. This book aims to familiarize readers with current knowledge on the mutual effects of sleep and mental health and provide an integrated framework for students, clinicians, and researchers. Throughout its 18 chapters, it discusses the six main categories of sleep disorders: insomnia (Chapters 3-5), hypersomnia (Chapters 6-7), sleep-disordered breathing (Chapters 8-11), circadian disorders (Chapters 12-13), parasomnias (Chapters 14-16), and sleep-related movement disorders (Chapters 17-18)"--